The role of gut microbiota in fetal methylmercury exposure: Insights from a pilot study. (3rd February 2016) - Rothenberg, Sarah E.; Keiser, Sharon; Ajami, Nadim J.; Wong, Matthew C.; Gesell, Jonathan; Petrosino, Joseph F.; Johs, Alexander
Graphical abstract: Highlights: Mercury methylation/demethylation did not likely contribute to stool methylmercury. Maternal stool mercury was not correlated with maternal hair or cord blood mercury. Seventeen bacterial genera were correlated with mercury in maternal stool or hair. For these correlations, gut microbiota functions (utilized or affected) are unknown. Abstract: Purpose: The mechanisms by which gut microbiota contribute to methylmercury metabolism remain unclear. Among a cohort of pregnant mothers, the objectives of our pilot study were to determine (1) associations between gut microbiota and mercury concentrations in biomarkers (stool, hair and cord blood) and (2) the contributions of gut microbial mercury methylation/demethylation to stool methylmercury. Methods: Pregnant women (36–39 weeks gestation, n = 17) donated hair and stool specimens, and cord blood was collected for a subset ( n = 7). The diversity of gut microbiota was determined using 16S rRNA gene profiling ( n = 17). For 6 stool samples with highest/lowest methylmercury concentrations, metagenomic whole genome shotgun sequencing was employed to search for the mercury methylation gene ( hgcA ), and two mer operon genes involved in methylmercury detoxification ( merA and merB ). Results: Seventeen bacterial genera were significantly correlated (increasing or decreasing) with stool methylmercury, stool inorganic mercury, or hair total mercury; however, aside from one genus, there was no overlap between biomarkers. There were no definitive matches for hgcA or merB, while merA was detected at low concentrations in all six samples. Major conclusions: Proportional differences in stool methylmercury were not likely attributed to gut microbiota through methylation/demethylation. Gut microbiota potentially altered methylmercury metabolism using indirect pathways.